The good trail - Geagan, Bill; Geagan, Bill. (New York : Coward-McCann Incorporated, 1954)
An author and naturalist retreats to the Maine woods to study nature and find God.
On the dust cover: How an author-naturalist learned about God and man from his days in the woods. Sequel to Nature I Loved.
Keywords: Natural history -- Maine; Radio programs -- Bangor (Me.); Newspapers -- Bangor (Me.); Nature; Naturalist; God; Outdoor life; Woodlands -- Maine